The role & impact of preservation architectural heritage on domestic tourism - M. Alnafeesi, Abdullah (2013)
Cultural and heritage tourism has become a major source of revenue for many communities and states across the globe. Heritage exploitation is currently a factor of human welfare and local development, raising new questions on preservation and safe guarding both material and tangible heritage. Domestic and regional tourism development is a key factor which contributes to economic welfare of the host country. Tourism destinations and businesses are becoming increasingly prone to the impacts of crises and disasters due to global environmental change and security risks. The major risk of depending upon the international tourism as a main source for regional tourism, it must show that domestic tourism as an alternative way of celebrating tourism without giving up to global pressures. This paper is to determine the link between architectural heritage and domestic tourism development.